Addition of Chemical and Osmotic Free Energies Through Negative Interaction of Protein-Bound Ligands - Weber, Gregorio (1972)
Simple free energy considerations show that an effector ligand, Y, bound to a protein can modify the standard free energy change of the reaction P - X + D - R = P - R + D - X, where P is a protein, D - R a small molecule, and X a group in the protein that interacts negatively with Y. By consideration of a three-compartment system containing the protein, an X-acceptor (A - R), an X-donor (D - X), and the ligand Y present at two different concentrations in the inner and outer compartments, it is shown that the protein can perform under steady-state conditions the addition of the free energy in the Y concentration gradient to that of the chemical reaction A - X + D - R = A - R + D - X. This free energy addition can effectively generate a high energy X-donor from a low energy one and may be of importance in metabolism, particularly in the oxidative phosphorylation of ADP.